A STUDY OF EFFICACY OF PEMETREXED BASED CHEMOTHERAPY IN ADVANCE MALIGNANT PLEURAL MESOTHELIOMA - ANKIT AGARWAL; RAMESH PUROHIT; AJAY YADAV; SHASHANK KOTHARI; AVI SHAH; ASHISH JAKHETIYA; RENU MISHRA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To study Clinicopathological profile & treatment outcomes of stage IV Malignant pleural mesothelioma (MPM) cases. Material and methods: The data obtained retrospectively was recorded in preformed proforma. Age, gender, hometown, residence, asbestos usage history, latent period between asbestos exposure and diagnosis, symptoms, histopathological type, stage, karnofsky performance (KPS), treatment regimen, survival were all recorded. Staging was done after histopathological confirmation of diagnosis using thoracic & abdominal Computed tomography, and/or PET CT. Patients were either treated with chemotherapy or immunotherapy. Results: 124 patients were diagnosed with MPM stage IV. Out of these 124 patients, 23 patients received only Oral metronomic chemotherapy (OMCT) due to poor Performance status (PS), 33 patients lost to follow up, 15 patients were given immunotherapy, and 53 patients were given palliative chemotherapy (pemetrexed plus carboplatin or cisplatin every 21 days until progression or intolerability). The median age at diagnosis was 63 years (41 yrs to 79 yrs). The male: female ratio was 2:1. Patients on palliative chemotherapy had response rate of 55% (29 patients out of 53 patients responded to chemotherapy). Median PFS and median OS for those patients on palliative chemotherapy was 3.9 months and 9.1 months respectively. The patients on OMCT had response rate of 27%, median PFS of 2.7 months and median OS of 6.9 months. Conclusion: We conclude that Advanced pleural mesothelioma has overall poor survival outcomes. Palliative pemetrexed based chemotherapy has shown better survival benefits in terms of OS & PFS as compared to OMCT alone.